Biochemical Evaluation of Properties of Klebsiella oxytoca Pectinase Isolated from Some Vegetable Wastes (Journal of Biochemistry, Microbiology and Biotechnology, 2025)
Pectinase is a group of enzymes that catalyze the breakdown of pectin. This study was carried out to investigate the biochemical and physicochemical properties of pectinase isolated from the fermentation of vegetable wastes using Klebsiella oxytoca. Pectinase was produced from Klebsiella oxytoca in a submerged fermentation system and purified in a three-step purification technique. The biochemical and physicochemical properties of purified pectinase were determined. The purified pectinase exhibited a subunit molecular weight of 46.34 kDa, specific activity of 164.87 mmol/min, and maximum stability at pH 6 and 50˚C. The enhancement of pectinase activity in the presence of Ca2+, Na+, Zn2+, and K+ aided the breakdown of pectin, while it was significantly reduced in the presence of Hg2+ and Mn2+. Some surfactants reduced the activity of the purified pectinase, while EDTA and ß-mercaptoethanol inhibited the enzyme. The estimated values of the kinetic constants, Vmax and Km, were 8.07 µmol/ml/min and 2.44 mM, respectively. The vegetable wastes produced by Klebsiella oxytoca and enzymes possess characteristic properties that may be suitable for use in industrial processes where pectinase is required.
Keywords: Pectinase; Klebsiella oxytoca; Purification; Physicochemical properties; Vegetable wastes